Ultrasonic-assisted extraction, analysis and properties of mung bean peel polysaccharide - Wenting Zhang; Wei Duan; Gangliang Huang; Hualiang Huang (Ultrasonics Sonochemistry, 2023)
In order to improve the yield of mung bean peel polysaccharide, on the basis of single-factor experiments, the ultrasonic assisted extraction conditions were optimized by response surface methodology (RSM). The results showed that under the conditions of material-liquid ratio of 1: 40, temperature 77 °C, ultrasonic power 216 W and extraction time 47 min, the extraction rate of mung bean peel polysaccharide was the best, which was 2.55 %. The extracted polysaccharide was phosphorylated and its antioxidant activity in vitro was studied. The results suggested that the modified polysaccharide had a significant scavenging effect on hydroxyl radicals and enhanced the ability of anti-lipid peroxidation, which offered ideas and methods for the development and application of mung bean peel polysaccharide.